2022
DOI: 10.1021/acs.jpca.2c01329
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory IR Spectra of the Ionic Oxidized Fullerenes C60O+ and C60OH+

Abstract: We present the first experimental vibrational spectra of gaseous oxidized derivatives of C 60 in protonated and radical cation forms, obtained through infrared multiple-photon dissociation spectroscopy using the FELIX free-electron laser. Neutral C 60 O has two nearly iso-energetic isomers: the epoxide isomer in which the O atom bridges a CC bond that connects two six-membered rings and the annulene isomer in which the O atom inserts into a CC bond connecting a fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We followed this approach in the current work and used a c value of 0.71 by testing a small set of experimental and computational spectra to give the best results. (Hedberg et al 1991, Hedberg et al 1997, Palotás et al 2019, Palotás et al 2022, Palotás et al 2021. It is shown that all the six basis sets are reasonable in reproducing the geometries of C 60 and C 70 , except that the experimental bond length of bond 8 of C 70 is much longer (the notation of C 70 bonds can be found in Figure A1 of the Appendix).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…We followed this approach in the current work and used a c value of 0.71 by testing a small set of experimental and computational spectra to give the best results. (Hedberg et al 1991, Hedberg et al 1997, Palotás et al 2019, Palotás et al 2022, Palotás et al 2021. It is shown that all the six basis sets are reasonable in reproducing the geometries of C 60 and C 70 , except that the experimental bond length of bond 8 of C 70 is much longer (the notation of C 70 bonds can be found in Figure A1 of the Appendix).…”
Section: Methodsmentioning
confidence: 89%
“…Also, Gerlich et al (2018) recently reported the gas-phase infrared spectrum of C 60 + using He-tagging technique in the spectral range of 1100-1600 cm -1 , but without detailed explanation on the origin of the measured features. Oomens and co-workers measured the infrared spectra of gas-phase C 60 H + , C 60 O + , C 60 OH + , and C 70 H + , using the infrared multiple photon dissociation (IRMPD) spectroscopy (Palotás et al 2019, Palotás et al 2022, Palotás et al 2021 and explored their possible relevance to the so-called "unidentified infrared emission" (UIE) bands which are ubiquitously seen at 3.3, 6.2, 7.7, 8.6, and 11.3 μm in a wide range of astrophysical regions. These elegant but challenging laboratory experiments are essential to fully understand the astronomical observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A joint experimental and theoretical approach proved to be a prospective method for the determination of substitution functional groups and their positions on fullerene cages, based on the comparison of experimental IR spectra of fullerene derivatives with theoretical ones. The dependence of the IR spectra upon the distribution of functional groups was successfully studied using DFT electronic structure calculations of hydroxylated [ 26 , 33 ] and oxidized [ 34 ] C 60 derivatives. Since the vibration frequencies of the carbon cage and oxygen–containing groups lie in the range of 1000–4000 cm −1 , this spectral energy region of fullerene derivatives is of special interest when determining the atomic structure of fullerenols by comparing the experimental and theoretical IR spectra [ 14 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, one manuscript reports that silicon carbide grains in conditions like those found in late-stage circumstellar envelopes will produce buckyballs and nanotubes, confirming in large part Nobel Laureate Sir Harry Kroto’s original idea about the astrophysical formation of these carbon allotropes. Examples of other novel molecules with potential astrochemical significance include 2-aza-1,3-butadiene, the C 7 H 5 radical, functionalized buckyballs in the form of C 60 O + and C 60 OH + , the 1-quinolinium (C 9 H 7 NH + ) cation along with its corresponding neutral and hydrogenated radicals, cyano-cyclopentadiene ions, the simplest aminooxycarbene in aminohydroxymethylene (H 2 N–C̈–OH), 1-cyanocyclobutene (C 5 H 5 N), monocyclic carbon ring cations of the form C 2 n + , the phenalenyl radical, and isomers of the PAH C 16 H 10 + . Purely theoretical studies are providing characterization for other unique molecules including glycolic acid, pyridyl radicals, and diazirine along with its cyclic isomers .…”
mentioning
confidence: 99%